WebTrace: An enhanced system for remote user interaction tracking and analysis in web applications - Jiseung Pyun; Min Heo; Yehui Choe; Jongwook Jeong (SoftwareX)
Usability testing is crucial for enhancing the user experience of web applications, yet traditional methods remain prohibitively costly and complex. In this paper, we present WebTrace, a tool that facilitates lightweight and effective usability testing by remotely tracking user interactions, such as clicks and keyboard inputs, through a browser extension. This simplifies testing and deployment across diverse environments. WebTrace also includes features to manage usability testing and abstract repetitive data, thereby enhancing analysis efficiency. By simplifying participation and supporting thorough analysis, WebTrace reduces the overall costs of usability testing while improving both time and resource management.